Four weeks of classical altitude training increases resting metabolic rate in highly trained middle-distance runners - Woods, A. L.; Sharma, A. P.; Garvican-Lewis, L. A.; Saunders, P. U.; Rice, A. J.; Thompson, K. G. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
High altitude exposure can increase resting metabolic rate (RMR) and induce weight loss in obese populations, but there is a lack of research regarding RMR in athletes at moderate elevations common to endurance training camps. The present study aimed to determine whether 4 weeks of classical altitude training affects RMR in middle-distance runners. Ten highly trained athletes were recruited for 4 weeks of endurance training undertaking identical programs at either 2200m in Flagstaff, Arizona (ALT, n = 5) or 600m in Canberra, Australia (CON, n = 5). RMR, anthropometry, energy intake, and hemoglobin mass (Hbmass) were assessed pre- and posttraining. Weekly run distance during the training block was: ALT 96.8 ± 18.3km; CON 103.1 ± 5.6km. A significant interaction for Time*Group was observed for absolute (kJ.day-1) (F-statistic, p-value: F(1,8)=13.890, p = .01) and relative RMR (F(1,8)=653.453, p = .003) POST-training. No significant changes in anthropometry were observed in either group. Energy intake was unchanged (mean ± SD of difference, ALT: 195 ± 3921kJ, p = .25; CON: 836 ± 7535kJ, p = .75). A significant main effect for time was demonstrated for total Hbmass (g) (F(1,8)=13.380, p = .01), but no significant interactions were observed for either variable [Total Hbmass (g): F(1,8)=1.706, p = .23; Relative Hbmass (g.kg-1): F(1,8)=0.609, p = .46]. These novel findings have important practical application to endurance athletes routinely training at moderate altitude, and those seeking to optimize energy management without compromising training adaptation. Altitude exposure may increase RMR and enhance training adaptation,. During training camps at moderate altitude, an increased energy intake is likely required to support an increased RMR and provide sufficient energy for training and performance